1996
DOI: 10.1557/proc-451-99
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Momolayers of Silicotungstate Anions on Ag(111) and Au(111) Electrode Surfaces

Abstract: ABSTRACTα-Dodecatungstosilicate (α-SiW12O404−) anions form ordered monolayers on Ag(111) and Au(111) surfaces. In-situ STM images reveal that the silicotungstate ion forms a square adlattice with an intermolecule spacing of 10.2 ± 0.5 Å on both Ag and Au surfaces. Additional structures exhibiting either row or rhombic motifs are observed on Au electrodes. The structure of the adlattices can be modeled using a simple model which maximizes the coordination of the silicotungstate ion to the electrode while mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 31 publications
4
30
0
Order By: Relevance
“…Early transition metal polyoxoanions have a strong affinity for metal surfaces, a property reflected in their efficacy as metal corrosion inhibitors c and d). In situ STM studies have revealed that ordered SiW 12 O 40 4- monolayers are formed spontaneously under these conditions, in the absence of an imposed potential.…”
Section: Self-assembly On Metal Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Early transition metal polyoxoanions have a strong affinity for metal surfaces, a property reflected in their efficacy as metal corrosion inhibitors c and d). In situ STM studies have revealed that ordered SiW 12 O 40 4- monolayers are formed spontaneously under these conditions, in the absence of an imposed potential.…”
Section: Self-assembly On Metal Surfacesmentioning
confidence: 99%
“…(b) A 50 × 50 nm 2 in situ STM image of a SiW 12 O 40 4- monolayer on Au(111) in 0.1 M aqueous H 2 SO 4 . (Reprinted with permission from ref . Copyright 1997 Materials Research Society.)…”
Section: Self-assembly On Metal Surfacesmentioning
confidence: 99%
“…STM 14 and AFM 15 images of bulk deposits of silicotungstate salts and related materials obtained following deposition and evaporation onto highly oriented pyrolytic graphite (HOPG) surfaces all show a hexagonal or quasi-hexagonal structure which is very different from the one observed on Ag(111). Moreover, the spontaneous ordering and persistence observed on Ag surfaces also differ from the behavior observed for bulk deposits of polyanions on HOPG and potential-induced assemblies of sulfate 16 and other anions [17][18][19] at the solid/liquid interface. Polyoxoanions are strongly adsorbed on HOPG, 17 Hg, 18 and Au(111) 19 surfaces, but ordered arrays are maintained only after imposition of relatively positive potentials.…”
mentioning
confidence: 99%
“…Moreover, the spontaneous ordering and persistence observed on Ag surfaces also differ from the behavior observed for bulk deposits of polyanions on HOPG and potential-induced assemblies of sulfate 16 and other anions [17][18][19] at the solid/liquid interface. Polyoxoanions are strongly adsorbed on HOPG, 17 Hg, 18 and Au(111) 19 surfaces, but ordered arrays are maintained only after imposition of relatively positive potentials. Selfassembly has heretofore not been observed.…”
mentioning
confidence: 99%
“…Through the oligomerization reactions, this class of compounds forms many structures in solution and the solid state ranging from MoO 4 2À to Mo 36 O 112 (H 2 O) 16 8À and beyond. 11 Molybdate is expected to associate with the growing platinum nanoparticle center because of a propensity to self-assemble on metal surfaces [12][13][14] and the previously demonstrated interaction of other oxometalates with metallic nanoparticles. [15][16][17][18][19] The amount and type of species associated with the Pt surface clearly depends strongly on the pH of the solution and the amount of molybdate added.…”
Section: Introductionmentioning
confidence: 99%